The efficacy and safety of angiogenesis inhibitors for recurrent ovarian cancer: a meta‑analysis - Chunmei Zhang; Wancheng Zhao (BMC, 2022)
Abstract Objective To investigate the efficacy and safety of angiogenesis inhibitors in the treatment of recurrent ovarian cancer (OC). Methods Electronic databases including PubMed, Web of Science, and the Cochrane Library were searched to find eligible studies until August 10, 2021. The data on overall survival (OS), progression-free survival (PFS), and objective response rate (ORR) were pooled. Furthermore, grade ≥ 3 adverse events (AEs) were investigated. Results A total of 13 studies with 3953 patients were included. Compared with control group, angiogenesis inhibitors resulted in significant improvement in PFS (hazard ratio (HR) = 0.61, 95%CI, 0.54-0.69), OS (HR = 0.88, 95%CI, 0.81-0.95), and ORR (odds ratio (OR) = 2.15, 95% CI, 1.74-2.65). However, angiogenesis inhibitors were associated with a higher risk of grade ≥ 3 AEs (relative risk (RR), 1.20, 95% CI, 1.04-1.38). Conclusion Angiogenesis inhibitors can improve ORR, PFS, and OS in patients with recurrent OC, but they can increase the incidence of AEs ≥ 3.